Semiotics and Translation in support of mother tongue teaching - Kourdis, Evangelos; Zafiri, Makrina (Signs - International Journal of Semiotics, 2010)
This paper includes a number of observations which derive from an interdisciplinary approach to teaching Greek as a mother tongue using the course books recommended by the Ministry of Education and Religious Affairs. Semiotics, translation and teaching are studied comparatively, perhaps for the first time in Greece, in an attempt to record the effectiveness of multi-semiotic texts in the teaching and learning of mother tongue in primary schools.